(untitled) (Journal of the College of Basic Education, 2022)
The research aims to find out whether there was a relationship between the numerical sense of multiple intelligences to the pupils the fifth grade, by testing hypotheses zero the following: - There is no statistically significant difference at the level of significance (0. 05) between the average test scores premise of common numerical and arithmetic average of the grades pupils in the fifth grade test numerical sense. There is no statistically significant difference at the level of significance (0.05) between the Mediterranean premise and the arithmetic average of the grades pupils in the fifth grade test multiple intelligences. There is no correlation statistically significant at the level of significance (0.05) between the scores of pupils in the fifth grade test scores and numerical sense to test multiple intelligences. Limited research on a sample of pupils fifth grade, as was the choice of four elementary schools simple random way in which each of the (school mark ornaments Primary School acumen primary, Blessed Rahman Primary School, School Eagles Elementary), and the Directorate of Education BAGHDAD / Rusafa first year the school from 2014 to 2015. The researchers used the research method descriptive, and the number of the respondents (240) schoolgirl, promising researchers two tests to measure the sense of numerical consisted of (12 items) and multiple intelligences consisted of (12 items) in mathematics from the multiple choice for both tests, and after the application of tests and treatment data statistically using Altaia test (T-tEST) for one sample and the Pearson correlation coefficient yielded the following results: - the low level of each of the sense of numerical and multiple intelligences to the pupils the fifth grade. The existence of a positive correlation statistically significant relationship between the sense of numerical mathematics and multiple intelligences In light of the findings the researchers recommended the use of teaching methods that stimulate and develop each of the numerical sense multiple intelligences and enrich the curriculum for students in the fifth grade positions stimulate and develop a sense of numerical and multiple intelligences. As a complement to search the researchers suggested conducting a pilot study to measure the impact of the use of modern teaching strategy in the sense of numerical and multiple intelligences development.